An intelligent pattern recognition system based on neural network and wavelet decomposition for interpretation of heart sounds - Turkoglu, I; Arslan, A (Ieee, 2001)
In this study, we develop a new automated pattern recognition system for interpretation of heart sound based on wavelet decomposition of signals and classification using neural network. Inputs to the system are the heart sound signals acquired by a stethoscope in a noiseless environment. We generate features for the objective concise representation of heart sound signals by means of wavelet decomposition. Classification of the features is performed using a back propagation neural network with adaptive learning rate. With two hundred record windows obtained from young humans are studied. One hundred of the record windows in database are selected for use as training phase for neural network. In the test result of the intelligent pattern recognition system with ten different types heart sound signals are acquired a high success.
23rd Annual International Conference of the IEEE-Engineering-in-Medicine-and-Biology-Society -- OCT 25-28, 2001 -- ISTANBUL, TURKEY
Keywords: heart sounds; phonocardiogram; wavelet decomposition; neural networks; pattern recognition